2010
DOI: 10.4067/s0718-19572010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Biology of little tunny Euthynnus alletteratus in the Gulf of Gabes, Southern Tunisia (Central Mediterranean Sea)

Abstract: Resumen.-Se describen algunos parámetros biológicos de la bacoreta Euthynnus alletteratus en el Golfo de Gabes (sur de Túnez), tales como la proporción de sexos, el Índice Gonado-Somático (IGS), el Índice Hepato-Somático (IHS), la longitud de primera madurez sexual, y la relación longitud-peso. Se analizó un total de 397 specímenes (244 hembras y 153 machos) entre los 36,7 y 97,8 cm de longitud, con un promedio 52,29 ± 5,87 cm. Las muestras se recolectaron mensualmente, entre enero de 2008 y diciembre de 2009.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…These differences between the Mediterranean and oceanic populations in the duration of the spawning season are also found in other species. For example, it has been reported that the spawning period of little tunny Euthynnus alletteratus (Rafinesque, 1810) in the central Mediterranean Sea is between June and September (Hajjej et al , 2010), whereas in the Atlantic Ocean the spawning season is between about April and November (Collette & Nauen, 1983). Likewise, the spawning period of the swordfish Xiphias gladius is shorter, between June and August, in the western Mediterranean Sea (De la Serna et al ., 1996) and between December and June in the north-west Atlantic Ocean (Arocha & Lee, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These differences between the Mediterranean and oceanic populations in the duration of the spawning season are also found in other species. For example, it has been reported that the spawning period of little tunny Euthynnus alletteratus (Rafinesque, 1810) in the central Mediterranean Sea is between June and September (Hajjej et al , 2010), whereas in the Atlantic Ocean the spawning season is between about April and November (Collette & Nauen, 1983). Likewise, the spawning period of the swordfish Xiphias gladius is shorter, between June and August, in the western Mediterranean Sea (De la Serna et al ., 1996) and between December and June in the north-west Atlantic Ocean (Arocha & Lee, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…If the existing information between ETA and NETAM areas is compared, in a study carried out in the ETA area, a very extensive spawning period is observed, which occupies practically the whole year [47]. However, in the Mediterranean Sea, the period is quite seasonal and limited, coinciding with the warmer period, between the months of June and August [49][50][51]69]. However, both biological aspects must be studied in depth in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Ikan tongkol merupakan sumberdaya hayati laut yang memiliki potensi nilai ekonomi cukup tinggi (Prayoga dkk., 2017). Ikan tongkol (Auxis sp) merupakan jenis ikan pelagis besar dan perenang cepat yang hidup secara bergelombol (Sompie, 2011;Hajjej et al, 2010;Sulistyaningsih et al, 2014). Pola kehidupan ikan tongkol tidak bisa dipisahkan dari adanya berbagai kondisi lingkungan, parameter oseanografi seperti suhu permukaan laut, salinitas, konsentrasi klorofil laut, cuaca dan sebagainya serta perubahan musim akan mempengaruhi kehidupan dan pertumbuhan ikan tongkol (Jalil, 2013).…”
Section: Pendahuluanunclassified